2018
DOI: 10.1088/1674-1056/27/1/016202
|View full text |Cite
|
Sign up to set email alerts
|

Ejecta from periodic grooved Sn surface under unsupported shocks

Abstract: Dynamic failure and ejection characteristics of a periodic grooved Sn surface under unsupported shock loading are studied using a smoothed particle hydrodynamics method. An "Eiffel Tower" spatial structure is observed, which is composed of high-speed jet tip, high-density jet slug, longitudinal tensile sparse zone, and complex broken zone between grooves. It is very different from the spike-bubble structure under supported shocks, and has been validated by detonation loading experiments. In comparison with tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 16 publications
2
12
0
Order By: Relevance
“…The direct effect of the interaction of the shock with the enough that the material breaks up into sharply defined 2579 layers, as also observed by [310].…”
supporting
confidence: 60%
“…The direct effect of the interaction of the shock with the enough that the material breaks up into sharply defined 2579 layers, as also observed by [310].…”
supporting
confidence: 60%
“…Since the incident shock wave is a triangular wave, the interface velocity continues to decay. The selfdeveloped 2D SPH code [25,26] is used to determine the peak stress and decay length of the incident triangular wave. Therefore, the stress profile of the incident triangular wave in shot 1 and shot 2 can be determined, as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The microspall simulations of tin are carried out using a self-developed 2D SPH code. [25,26] In the SPH method, the material is discretized into a series of particles with independent information. Due to its Lagrangian nature, SPH has the advantage of simulating free-surface flows with large deformations.…”
Section: Model and Methodsmentioning
confidence: 99%
“…Theoretically, Piriz et al [23] proposed an analytical model based on the linear Richtmyer-Meshkov instability (RMI) in solids under the conditions of high-energy-density, and showed that plasticity determined the maximum perturbation amplitude and provides simple scaling laws. Besides, molecular dynamics (MD) [1,12,24,25], Eulerian [14,26,27], and smoothed particle hydrodynamics (SPH) [28][29][30] methods have all been used to simulate the microjet formation. Dimonte et al [31] described a simple algebraic model for the microjet based on the hydrodynamics and MD simulations of the RMI.…”
Section: Introductionmentioning
confidence: 99%
“…Shao et al [11,13,33] presented the effects the shockwave profile on the microjet morphology and mass with MD simulations. Besides, Wang et al [28,34] discussed the dependence of microjet on the shock wave front with SPH simulations. The systematic understanding of the microjet induced by supported shock has been achieved, but the influence of shock profile on microjet is still lack of pertinent research and only a few comparisons of the triangular waves and supported waves reported [12,28,33].…”
Section: Introductionmentioning
confidence: 99%